Acute postoperative sepsis mimicking symptomology suspicious for malignant hyperthermia: case report - Ramanujam,Vendhan (2019)
Abstract Background: Sepsis is a life-threatening organ dysfunction with non-specific clinical features that can mimic other clinical conditions with hyper metabolic state such as malignant hyperthermia. Perioperatively anesthesia providers come across such scenarios, which are extremely challenging with the need for urgent intervention. Objective: To illustrate the need for early intervention and consultation for added assistance to approach and rule out malignant hyperthermia and other possible causes during such a scenario. Case report: A 63-year-old male underwent an uneventful elective flexible cystoscopy and transrectal ultrasound-guided prostate biopsy. Postoperatively he developed symptoms raising suspicion for malignant hyperthermia. Immediately malignant hyperthermia protocol was initiated that included administration of dantrolene and consultation of malignant hyperthermia association hotline along with other diagnostic and interventional management aimed at patient optimization. While early administration of dantrolene helped in hemodynamically stabilizing the patient, the consultation with other providers and malignant hyperthermia association hotline along with repeated examinations and lab works helped in ruling out malignant hyperthermia as the possible diagnosis. The patient later recovered in the intensive care unit where he was treated for the bacteremia that grew in his blood cultures. Conclusions: Sepsis shares clinical symptoms that mimic malignant hyperthermia. While sepsis rapidly progresses to secondary injuries, malignant hyperthermia is life threatening. Providing ideal care requires good clinical judgment and a high level of suspicion where timely and appropriate care such as early administration of dantrolene and consultation of malignant hyperthermia association hotline for added assistance can influence positive outcomes.